Pendampingan Manajemen Keuangan UMKM dalam Penyusunan Pembukuan Usaha Sederhana - Karona Cahya Susena; Nenden Restu Hidayah; Heskyel Pranata Tarigan; Nevi Fitriani (Universitas Dehasen Bengkulu, 2025)
Financial management is an essential aspect of the sustainability of micro, small, and medium enterprises. However, several MSME actors in Bengkulu City still face difficulties in recording transactions, separating personal and business finances, and preparing simple financial reports. This community service activity aims to improve MSME actors’ ability to prepare simple business bookkeeping through financial management assistance. The implementation method included partner needs identification, pre-test, financial recording training, cash book preparation practice, mentoring, post-test, and evaluation. The activity involved 25 MSME actors in Bengkulu City. The results showed an increase in participants’ average understanding from 46 in the pre-test to 78 in the post-test, or an improvement of 69.6%. In addition, participants began to record daily transactions, separate personal and business finances, and prepare simple cash reports. This activity indicates that practice-based mentoring can improve MSME financial management skills and support more structured business decision-making